(untitled) (The Peerian Journal, 2024)
The study is centered on compounds derived from Nigella sativa and Senna alata; extraction, identification and quantification methods of which are the focus of this study together with a focus on newer analytical techniques. These plants are known for their healing properties, namely, bactericidal, anti-inflammatory and anti-oxidative activity. The study seeks to observe these compounds with a view of determining their capacity in the creation of therapies